2021
DOI: 10.3390/app11083682
|View full text |Cite
|
Sign up to set email alerts
|

Some of the Physical and Mechanical Properties of Particleboard Made from Betung Bamboo (Dendrocalamus asper)

Abstract: The objective of this study was to evaluate various physical and mechanical properties of experimental particleboard panels made from Asian giant bamboo (Dendrocalamus asper). Single layer panels having a density level of 0.75 g/cm3 from coarse and fine particles were used within the scope of this study. Thickness swelling, water absorption, surface roughness, and wettability characteristics of the samples were tested as physical properties while bending, internal bond strength, and screw withdrawal strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Many straw‐based particleboards with weak bonding strength were owing to the low rigidity of materials, which was usually blended with wood particles to improve the strength 17 . MOR and IBS of RPs were obviously higher than those of many other non‐wood‐based particleboards and even particleboards made from wood 30–33 . The mechanical strength of particleboards is not only affected by the structure of biomass, but also by the formation process.…”
Section: Resultsmentioning
confidence: 99%
“…Many straw‐based particleboards with weak bonding strength were owing to the low rigidity of materials, which was usually blended with wood particles to improve the strength 17 . MOR and IBS of RPs were obviously higher than those of many other non‐wood‐based particleboards and even particleboards made from wood 30–33 . The mechanical strength of particleboards is not only affected by the structure of biomass, but also by the formation process.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of group A, even though particleboard with fine particles had higher density, the ESW was lower than particleboard with coarse particles. The recorded FSW in group C was 693 to 1079 N and the ESW was 1665 to 2394 N. As a result, it can be concluded that particle size is an important parameter in single layer particleboard to achieve the properties desired for specific applications [19].…”
Section: Effects Of Particle Size and Combination On Mechanical Prope...mentioning
confidence: 87%
“…Particles with a high aspect ratio (Length/Thickness) provide a larger surface area for adhesive contact, and besides, particles with a low aspect ratio and small size serve as fillers to fill the void between larger particles [18]. The effect of particle size on particleboard has been extensively studied; recently Karlinasari et al and Bazzetto et al reported coarse particles could have better physical and mechanical properties compared to fine particles in the production of single-layer particleboard with bamboo, however, analysis of IB has shown fine particles are better at bonding due to their vast surface area [19,20]. Based on the results of Hegazy and Ahmed, fine particles provide better bending strength (BS) and IB properties when producing particleboard with Date Palm, however, thickness swelling is not significantly affected by fine particles [21].…”
Section: Introductionmentioning
confidence: 99%
“…All the boards were air dried to a moisture content of around 9%. Two papers by Karlinasari et al [5,12] outlined the technique for obtaining fine and coarse particles, as well as the manufacturing of particle board panels. Following that, the board samples were cut into circular discs with a diameter of 10 cm and 3 cm for acoustical characteristics testing.…”
Section: Methodsmentioning
confidence: 99%